2019
DOI: 10.1111/and.13342
|View full text |Cite|
|
Sign up to set email alerts
|

Favourable effect of β‐glucan treatment against cisplatin‐induced reproductive system damage in male rats

Abstract: The aim of this study was to investigate the potential beneficial effects of β‐glucan treatment against oxidative, histological and spermatological damage caused by cisplatin on the male reproductive system. Twenty‐eight Sprague Dawley male rats were used in the study. The rats were randomly divided into four equal‐sized groups: a control group, cisplatin group (7 mg/kg in a single‐dose cisplatin administered intraperitoneally), β‐glucan group (β‐glucan given at a dose of 50 mg kg−1 d−1 for 14 day) and a cispl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Many studies have shown that β-glucan plays an important role in inhibiting inflammatory damage [30][31][32]. The protective effect is closely related to the antioxidant and anti-inflammatory cytokines induced by β-glucan.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that β-glucan plays an important role in inhibiting inflammatory damage [30][31][32]. The protective effect is closely related to the antioxidant and anti-inflammatory cytokines induced by β-glucan.…”
Section: Discussionmentioning
confidence: 99%
“…In the article (Kaya et al, 2019), it has come to our attention that the published version of Table 1 is incorrect.…”
Section: Groups Tbars Nmol/g Tissue Reduced Gsh Nmol/g Tissue Cat K/mg Protein Sod U/mg Protein Gpx U/mg Proteinmentioning
confidence: 99%